Encyclopaedic preservation or performative act? The translation of Latin charms in the Old English Medicina de quadrupedibus - Omar Khalaf (Filologia Germanica)
The Old English translation of the Medicina de quadrupedibus belongs to the corpus of early medieval English materia medica. This small treatise brings together remedies for various diseases taken from parts of animals, often to be applied along with uttering a series of charms. Traditionally deemed as devoid of the originality that characterizes genuinely insular works of the same type as the Lacnunga and Bald’s Læceboc, Medicina de quadrupedibus has not aroused particular interest among critics of early English medical lore, nor have the charms contained in it been object of close investigations. Nevertheless, the translation of these charms from Latin raises important linguistic and stylistic questions with regard to their reception and potential use. In this article I argue that the linguistic and rhythmic elements introduced in the Old English versions are recognizable as typically oral-formulaic and, consequently, suggest a rewriting based on their possible oral performance.